2007
DOI: 10.1109/tcsi.2006.887977
|View full text |Cite
|
Sign up to set email alerts
|

A CMOS ISFET Interface Circuit With Dynamic Current Temperature Compensation Technique

Abstract: This paper presents a new ion-sensitive field-effect transistor (ISFET ) readout circuit including a novel nonlinear temperature compensation method that is based on the theoretical work for formulating a body-effect-based ISFET drain current expression, the derivation of an unified temperature-dependent ISFET threshold voltage expression, and the use of iterative method for solving design parameters in nonlinear equations. Regarding the basic readout circuit, it comprises only one source follower and one curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…The first phenomenon is a result of the drift mechanism [5], as well as slow pH response [6]- [8], which poses challenges in maintaining the long-term stability of standard ISFET devices. The second phenomenon is a result of the pH dependent temperature coefficient [9], [11]- [13] and nonlinear temperature dependent mobility in MOS part of ISFET [17], [24], which increase the difficulty of thermal compensation. Furthermore, it has been reported that the ISFET drift rate has an exponential incremental tendency, with increasing pH value, as well as temperature value [25].…”
Section: Introductionmentioning
confidence: 99%
“…The first phenomenon is a result of the drift mechanism [5], as well as slow pH response [6]- [8], which poses challenges in maintaining the long-term stability of standard ISFET devices. The second phenomenon is a result of the pH dependent temperature coefficient [9], [11]- [13] and nonlinear temperature dependent mobility in MOS part of ISFET [17], [24], which increase the difficulty of thermal compensation. Furthermore, it has been reported that the ISFET drift rate has an exponential incremental tendency, with increasing pH value, as well as temperature value [25].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical threshold voltage consists of two potentials -eo + sol , sol in which is a constant with respect to the pH value, and eo is the only chemical parameter that is responsible for pH sensitivity of EGFET. sol , with a typical value of 50 mV, is the surface dipole potential of the solvent being independent of pH (Chan et al, 2007). The sensitivity of eo , which is defined as the change of eo with respect to a change of the pH value of the solution Δ eo /ΔpH , has already been explained by the Hal and Eijkel's theory (Van Hal et al, 1995).…”
Section: Egfet-operational Amplifiermentioning
confidence: 99%
“…It has appreciable advantages over traditional glass-electrode sensors on the basis of its small size, robustness, simplicity in fabrication and low cost (Yin et al, 1999). Moreover, many research works have exploited different circuit architectures of readout circuits, which usually play the role in translating the values to voltage domain presentation, with the goal to obtain good sensitivity as well as linearity (Chan et al, 2007). However, the conventional readout circuitry of pH sensor comprises multiple chips and discrete components which are fabricated in different technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The ion sensitive field effect transistor (ISFET) used as a pH sensor is an integrated device composed of a conventional ion selective membrane and a metal oxide semiconductor field effect transistor (MOSFET) [1][2][3][4]. Extended gate field effect transistor (EGFET) is another structure to isolate FET from chemical environment, in which a sensitive membrane is fabricated on the end of the signal line extended from the gate electrode of field effect transistor [5]. Therefore, EGFET is more convenient for package and manufacture using CMOS processes.…”
Section: Introductionmentioning
confidence: 99%